2014
DOI: 10.1021/ja506664a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Accumulation of Aromatic Aldehydes in an Engineered Strain of Escherichia coli

Abstract: Aromatic aldehydes are useful in numerous applications, especially as flavors, fragrances, and pharmaceutical precursors. However, microbial synthesis of aldehydes is hindered by rapid, endogenous, and redundant conversion of aldehydes to their corresponding alcohols. We report the construction of an Escherichia coli K-12 MG1655 strain with reduced aromatic aldehyde reduction (RARE) that serves as a platform for aromatic aldehyde biosynthesis. Six genes with reported activity on the model substrate benzaldehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
299
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 270 publications
(318 citation statements)
references
References 70 publications
4
299
0
3
Order By: Relevance
“…At the same time, the enzymatic background of bacterial cells rapidly reduces aldehydes ( b ) to the corresponding alcohols ( c ) which minimizes the oxidative and electrophilic stress responses induced by the reactive carbonyl group in aldehydes. [39,41] To circumvent b reduction, we opted for E. coli K‐12 MG1655 RARE42 – a knock‐out strain with r educed aromatic a ldehyde re duction – as a host for whole cell mediated aldehyde preparation. Despite this deliberate choice, initial experiments towards the reduction of the model substrate cinnamic acid 1a to 1b showed significant amounts of the undesired alcohol 1c .…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the enzymatic background of bacterial cells rapidly reduces aldehydes ( b ) to the corresponding alcohols ( c ) which minimizes the oxidative and electrophilic stress responses induced by the reactive carbonyl group in aldehydes. [39,41] To circumvent b reduction, we opted for E. coli K‐12 MG1655 RARE42 – a knock‐out strain with r educed aromatic a ldehyde re duction – as a host for whole cell mediated aldehyde preparation. Despite this deliberate choice, initial experiments towards the reduction of the model substrate cinnamic acid 1a to 1b showed significant amounts of the undesired alcohol 1c .…”
Section: Resultsmentioning
confidence: 99%
“…After deletion of six genes that encode enzymes with confirmed activity on benzaldehyde in vitro (dkgA, dkgB, yeaE, yahK, ahr, and yqhD), the engineered E. coli strain accumulated benzaldehyde and vanillin with minimal alcohol formation and was thus dubbed "RARE" for displaying reduced aromatic aldehyde reduction (Addgene catalog no. 61440) (43). Each targeted gene was capable of causing reduction of benzaldehyde and vanillin in vivo when individually overexpressed in the RARE background.…”
Section: Minimizing Endogenous Conversion Of Aldehydes To Alcoholsmentioning
confidence: 99%
“…Each targeted gene was capable of causing reduction of benzaldehyde and vanillin in vivo when individually overexpressed in the RARE background. However, the use of deletion subset strains and quantitative reverse transcription-PCR (qRT-PCR) revealed that deletions of dkgB and yeaE did not contribute to aldehyde accumulation under the conditions tested due to low native expression of these genes (43).…”
Section: Minimizing Endogenous Conversion Of Aldehydes To Alcoholsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Figura 1 apresenta os cromatogramas obtidos por GC/MS do cultivo de Phormidium com monossacarídeos no tempo 96 horas com seus respectivos aldeídos em destaque. A diminuição da concentração se explica pela rápida conversão de aldeídos em álcoois por uma numerosa quantidade de enzimas endógenas presente em micro-organismos (Kunjapur et al, 2014), justificando a formação de álcoois significativamente alta no final de 144h. Dos componentes identificados em ambos os cultivos, 3-metilbutanal (2,2 µg/mg) destaca-se como majoritário no período de 144h, seguido pelo 3-octenal (2,1 µg/mg).…”
Section: Resultado E Discussãounclassified